Efeitos do liofilizado do extrato hidroalcoólico da casca da raiz de Dioclea grandiflora Martius ex Bentham em ratos diabéticos com disfunção erétil - Assis, Valeria Lopes de (2016)
Dioclea grandiflora is a Leguminosae family plant, exclusive of the Brazilian Caatinga. Studies have shown various pharmacological properties of extracts or components of the plant, such as antioxidant properties and beneficial effects on the cardiovascular system. However, there are no reports on its activity in erectile function.Thus, this study aimed to characterize the lyophilized of the hydro-alcoholic extract of the bark of D. grandiflora root (LEHDg) and to assess its effect on erectile function of normoglycemic and diabetic rats. To this end, in vivo and in vitro experimental assays were used. LEHDg showed great concentration of phenolic compounds by Folin-Ciocalteu methods and high-performance liquid chromatography (HPLC). Also, this lyophilized demonstrated potent anti-free radical activity against DPPH● radical. In rats corpus cavernosum preparations (CC) pre-contracted by phenylephrine, LEHDg induced concentration dependent relaxation. However, this response was significantly reduced in the presence of L-N-nitro-arginine methyl ester (L-NAME) NOS inhibitor; 2-(4-phenyl)-4,4,5,5-tetrametilimidazolina-1-oxy-3-oxide potassium salt (PTIO), the NO radical scavenger and 1H-[1,2,4] oxadiazole [4,3-a] quinoxalin-1-one (ODQ) cyclase inhibitor of soluble guanylyl (CGs), suggesting the involvement of via NOS/NO/CGs in its relaxing effect. The antioxidant activity of LEHDg was evaluated in CC cuts treated by dihidroetid probe (DHE). This lyophilized has reduced the basal fluorescence levels of this probe when compared to the control and the positive control (apocynin), proving antioxidant action. Given these results, we investigated the action of LEHDg on erectile dysfunction (ED) in streptozotocin (STZ) induced diabetic rats. The rats were divided into 5 groups: control group (non-diabetic), STZ group and three STZ groups treated with LEHDg (25 or 37.5 mg/kg) or sildenafil (1.5 mg/kg), which were treated with 28 days. In diabetic rats, body weight decreased and glucose levels increased, when compared to the control group. Treatment with LEHDg or sildenafil did not affect these parameters. Erectile function was assessed by the ratio intracavernous pressure/mean arterial pressure (ICP/MAP). The ICP/MAP in diabetic groups was significantly reduced when compared to the control group. Treatment with sildenafil or LEHDg promoted improvement of this parameter, suggesting a reduction of ED by these treatments. In CC preparations, the maximum contractile response to phenylephrine was significantly increased in diabetic rats compared to controls. Treatments with LEHDg or sildenafil reduced this hypercontractility. Likewise, a significant increase in contractile response induced by electrical field stimulation in CC of diabetic animals, however, only treatment with LEHDg 37.5 mg/kg reduced this effect. The relaxing response induced by acetylcholine was significantly reduced in CC of diabetic animals when compared to the control group. This effect was reversed by treatment with LEHDg or sildenafil. In CC cuts, treatment with sildenafil or LEHDg significantly reduced basal fluorescence of DHE probe when compared to diabetic animals. These results demonstrate that LEHDg is rich in phenolic compounds with potent antioxidant activity that promotes relaxation in CC via NOS/NO/CGs. In animals with diabetes induced ED, LEHDg promotes improvement in erectile function, as well as improved endothelial function, decreased hypercontractility and reducing oxidative stress in the corpus cavernosum.